2011
DOI: 10.1111/j.1744-7402.2009.02440.x
|View full text |Cite
|
Sign up to set email alerts
|

Subcritical Crack Growth Behavior of A Perovskite‐Type Oxygen Transport Ceramic Membrane

Abstract: We herein report subcritical crack growth (SCG) studies of La 0.2 Sr 0.8 Fe 0.8 Cr 0.2 O 3Àd (LSFCO) perovskite membranes as oxygen transport membranes (OTM). Two sample batches of perovskite were tested to investigate the effect of temperature, specific chemical environments, and loading rate on flexure strengths, using four-point bend tests. The first batch was examined at room temperature in air. The second batch was soaked in an N 2 /air atmosphere at 10001C. Stress rates varied approximately from 0.2 to 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…However, the value of n of BSCF decreases dramatically to 13.83 as temperature rises to 800°C, which is approximately 43% of the value at room temperature. A similar trend has been also found in other perovskite‐structured materials . It indicates that BSCF is much more sensitive to SCG at 800°C.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…However, the value of n of BSCF decreases dramatically to 13.83 as temperature rises to 800°C, which is approximately 43% of the value at room temperature. A similar trend has been also found in other perovskite‐structured materials . It indicates that BSCF is much more sensitive to SCG at 800°C.…”
Section: Discussionsupporting
confidence: 84%
“… Using the SCG parameter n = 24.32 and σ 0 = 77 MPa in Equation , the equivalent stress that would result in the failure of the sample in 1 second is 78.42 MPa. Combination of this stress and 1 − F = 1/e (corresponding to the characteristic strength σ 0 ; e is Euler's constant), where F is failure probability, shows the first data point of the 1 second line on the SPT diagram. Plot the 1 second line with a slope of Weibull modulus 10.2. A series of lines parallel to the 1 second line, with spacing between the lines equaling to (ln 10)/n or 2.3/n. The spacing 2.3/n represents a change in life‐time by a factor of 10 . Each line represents a decade increase in lifetime. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The loading rate sensitivity of bending test data can be used to assess the slow crack growth sensitivity of a material. It has been shown that the strength is linked to a particular stress rate σ via [4,5]:…”
Section: Slow Crack Growth (Scg)mentioning
confidence: 99%
“…SCG is generally not well addressed for perovskite type ceramic membrane materials. For the perovskite La 0.2 Sr 0.8 Fe 0.8 Co 0.2 O 3 -δ (LSFC) SCG has been investigated [4]. The SCG is investigated in the present work measuring the stress rate dependence of the fracture strength [5].…”
Section: Introductionmentioning
confidence: 99%